2014
DOI: 10.1136/oemed-2013-101987
|View full text |Cite
|
Sign up to set email alerts
|

Urinary polycyclic aromatic hydrocarbon biomarkers and diabetes mellitus

Abstract: Objective The aim of the current study is to investigate the association of polycyclic aromatic hydrocarbons (PAHs), a group of environmental pollutants, with diabetes mellitus. Animal studies link PAHs to inflammation and subsequent development of diabetes mellitus. In addition, occupational studies suggest that exposure to other aromatic hydrocarbons such as dioxins may be associated with diabetes risk in humans. Design We examined participants from the merged National Health and Nutrition Examination Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 29 publications
2
38
2
1
Order By: Relevance
“…The incremented incidence of dietary intake of PAHs has resulted in the metabolism defects due to their persistent bioaccumulation in food chain. The PAHs' resistance against degradation hinders the metabolic activity of glucose homeostasis and β-cell function to act as the potential cause of the Type 2 diabetes (T2DM) (Andersen et al, 2012;Raaschou-Nielsen et al, 2013;Alshaarawy et al, 2014). These non-genotoxic effects of the continuous environmental and dietary (charred and broiled meat) exposure has become one of the significant casual factors contribution to the development of metabolic syndrome in terms of dyslipidemia and raised blood pressure (Hu et al, 2015).…”
Section: Classification Of Pah and Their Toxicitymentioning
confidence: 99%
“…The incremented incidence of dietary intake of PAHs has resulted in the metabolism defects due to their persistent bioaccumulation in food chain. The PAHs' resistance against degradation hinders the metabolic activity of glucose homeostasis and β-cell function to act as the potential cause of the Type 2 diabetes (T2DM) (Andersen et al, 2012;Raaschou-Nielsen et al, 2013;Alshaarawy et al, 2014). These non-genotoxic effects of the continuous environmental and dietary (charred and broiled meat) exposure has become one of the significant casual factors contribution to the development of metabolic syndrome in terms of dyslipidemia and raised blood pressure (Hu et al, 2015).…”
Section: Classification Of Pah and Their Toxicitymentioning
confidence: 99%
“…Because air pollution and cigarette smoking are important sources of PAHs, both have been consistently linked to cardiometabolic diseases such as diabetes (Chang, 2012), the biological plausibility could suggest that PAHs may play an important role in the relationship between cigarette smoking, ambient air pollution, and cardiometabolic diseases. A recent study found that PAHs are associated with prevalence of diabetes among adults in the United States (Alshaarawy et al, 2014); however, the underlying mechanism for this relationship is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently the European Food Safety Authority has made a detailed assessment of human exposure from dietary sources (EFSA, 2008). In addition to the cancer risk, PAH exposure has been linked to the onset of diabetes mellitus (Yang et al 2014;Alshaarawy, et al 2014), metabolic syndrome (Brocato et al 2014;Hu et al 2015), and cardiovascular conditions (Xu et al 2010;Feng et al 2014). Since all exposure sources can contribute to the body burden of PAH, quantitative evaluation of exposure pathways is important if health risk is to be minimised.…”
Section: Introductionmentioning
confidence: 99%